2015
DOI: 10.3346/jkms.2015.30.10.1459
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Residual Volume/Total Lung Capacity in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The prognostic role of resting pulmonary hyperinflation as measured by residual volume (RV)/total lung capacity (TLC) in chronic obstructive pulmonary disease (COPD) remains poorly understood. Therefore, this study aimed to identify the factors related to resting pulmonary hyperinflation in COPD and to determine whether resting pulmonary hyperinflation is a prognostic factor in COPD. In total, 353 patients with COPD in the Korean Obstructive Lung Disease cohort recruited from 16 hospitals were enrolled. Restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
(50 reference statements)
1
41
0
Order By: Relevance
“…Increased RV/TLC is associated with small airway disease, frequent exacerbations of COPD, and increased mortality in patients with COPD. [20][21][22][23] In addition, we assumed that the component of bronchial wall thickening was added to the emphysema component, which eventually contributed to poor outcome. Chronic bronchitis patients with COPD are characterized by airway wall thickening as detected via thoracic CT. 6,14 Such patients are often more symptomatic and show more frequent exacerbations compared to patients without chronic bronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased RV/TLC is associated with small airway disease, frequent exacerbations of COPD, and increased mortality in patients with COPD. [20][21][22][23] In addition, we assumed that the component of bronchial wall thickening was added to the emphysema component, which eventually contributed to poor outcome. Chronic bronchitis patients with COPD are characterized by airway wall thickening as detected via thoracic CT. 6,14 Such patients are often more symptomatic and show more frequent exacerbations compared to patients without chronic bronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…As a parameter used to define the presence of airflow limitation, FEV1/FVC ratio has been recommended as an index to diagnose patients with COPD and those at risk, and a low FEV1/FVC ratio after bronchodilator use might indicate the need for corticosteroid therapy in mild asthma [ 29 31 ]. The differences in pulmonary function index in patients with asthma, AECOPD, and ACOS could help to diagnose these 3 diseases more quickly and accurately, which is of great clinical importance [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hyperinflation predicts exercise capacity 3 and is measured by the 6-minute walk test (6MWT), which has been clearly correlated with mortality in COPD patients. Recently, Rim Shin et al 4 confirmed that, in addition to advanced age, both raised RV/TLC and a short 6-minute walking distance are independent predictors for all-cause mortality. -Multidimensional indices.…”
Section: Predictors Of Mortality In Chronic Obstructive Pulmonary Dismentioning
confidence: 91%